ACCOUNTING CASH FLOWS OF THE ORGANIZATION - Карданова, Зурят; Тхаркахова, Ирина; Понокова, Данная (SWorldJournal, 2020)
The article proves the relevance of the research topic, as the competent organization of cash flow accounting, is the basis for making rational management decisions, contributes to increasing the resilience of the economic entity to external and external